Retention of resin-based filled and unfilled pit and fissure sealants: A comparative clinical study - V Rajashekar Reddy; Nagalakshmi Chowdhary; K S Mukunda; N K Kiran; B S Kavyarani; M C Pradeep (Wolters Kluwer Medknow Publications, 2015)
Background and Objectives: The most caries-susceptible period of a permanent first molar tooth is the eruption phase, during which the enamel is not fully matured and it is usually difficult for the child to clean the erupting tooth surfaces. Sealing occlusal pits and fissures with resin-based pit and fissure sealants is a proven method to prevent occlusal caries. The difference in the viscosity of the sealants differs in the penetration into pit and fissures and abrasive wear resistance property due to the addition of filler particles. The present study was conducted to evaluate and compare the retention of the resin-based filled (Helioseal F, Ivoclar Vivadent) and unfilled (Clinpro, 3M ESPE) pit and fissure sealants, which is important for their effectiveness. Materials and Methods: Fifty-six children between the age group of 6 and 9 years, with all four newly erupted permanent first molars were selected. Sealants were applied randomly using split mouth design technique on permanent first molars. Evaluation of sealant retention was performed at regular intervals over 12 months, using Simonsen's criteria at 2 nd , 4 th , 6 th , 8 th , 10 th and 12 th month. The results were subjected to statistical analysis. Results: At the end of our study period (12 th month), 53.57% showed complete retention, 37.50% showed partial retention, and 8.83% showed complete missing of resin-based filled (Helioseal F) pit and fissure sealant. And, 64.29% showed complete retention, 32.14% showed partial retention, and 3.57% showed complete missing of resin-based unfilled (Clinpro) pit and fissure sealant. This difference in retention rates between filled and unfilled pit and fissure sealants was not statistically significant. Conclusion: The difference in retention rates between Helioseal F and Clinpro was not statistically significant, but Clinpro (unfilled) sealant showed slightly higher retention rates and clinically better performance than Helioseal F (filled).